Synchronization in a Wireless Sensor Network Designed for Surveillance Applications - Fernandez, J.A.S.; Hernando, A.B.G.; Ortega, J.F.M.; Santidrian, L.L. (2009 Fifth International Conference on Wireless and Mobile Communications, 2009)
System dynamics and algebraic graph theory provide the mathematical framework to understand the dynamical and topological features of complex networks, among them the synchronization properties of wireless sensor networks (WSN), a far from trivial subject that may be of great importance for many WSN applications. In this paper, we apply some of these mathematical tools to assess the ease of synchronization of a WSN which has been specifically designed to support surveillance applications.